The satisfaction level of Surabaya's community regarding the "Good Morning" news program on CNN Indonesia at Trans TV - Ayu Nensi Dua (DIGICOM : Jurnal Komunikasi dan Media, 2023)
Television news is one of the television programs that almost owned by all the private television stations and the government. Through the news of television show, the viewers can find a variety of important and interesting information inside and outside the country, then get more information of government, economic, criminal, disaster, etc. This study aims to find out the audience’s satisfaction in watching CNN Indonesia Good Morning news program on Trans TV. The sample used 100 people by using Slovin techniques, in which only Surabaya citizen who had watched Indonesian CNN news programs at least 3 times. Furthermore, the audience satisfaction is measured by using Gratification Sought (GS) and Gratification Obtained (GO) approaches. The result shows that the audience gained the satisfaction from fulfilling the information motives with a significant gap value in watching the Good Morning CNN Indonesia news program on Trans TV. However, the audience did not get satisfaction from fulfilling the personal identity motives with insignificant gap values. Moreover, the audience gained the satisfaction from fulfilling of the integration and social interaction motives with a significant gap value, and then the audience also obtained the satisfaction from fulfilling the entertainment motives with insignificant gap values. In general, the audience gets the fulfilment of satisfaction from the information motives, the integration and social interaction motives. It means that the information, integration, and social interaction contents presented by Good Morning CNN Indonesia news is sufficient to meet the needs of the audience. The results of this study can be used as a good input for the manager of Good Morning CNN Indonesia news program on Trans TV to maintain the information content, the social integration and interaction content, and also to strengthen the news content of the personal identity and entertainment.